Plant microRNAs from Moringa oleifera Regulate Immune Response and HIV Infection - Antonella Minutolo; Marina Potestà; Valentina Roglia; Marco Cirilli; Marco Cirilli; Federico Iacovelli; Carlotta Cerva; Joseph Fokam; Alessandro Desideri; Massimo Andreoni; Sandro Grelli; Vittorio Colizzi; et al. (Frontiers Media S.A., 2021)
Traditional medicine is often chosen due to its affordability, its familiarity with patient's cultural practices, and its wider access to the local community. Plants play an important role in providing indispensable nutrients, while specific small RNAs can regulate human gene expression in a cross-kingdom manner. The aim of the study was to evaluate the effects of plant-enriched purified extract microRNAs from Moringa oleifera seeds (MO) on the immune response and on HIV infection. Bioinformatic analysis shows that plant microRNAs (p-miRs) from MO belonging to 18 conserved families, including p-miR160h, p-miR166, p-miR482b, p-miR159c, p-miR395d, p-miR2118a, p-miR393a, p-miR167f-3p, and p-miR858b are predicted to target with high affinity BCL2, IL2RA, TNF, and VAV1, all these being involved in the cell cycle, apoptosis, immune response and also in the regulation of HIV pathogenesis. The effects of MO p-miRs transfected into HIV+ PBMCs were analyzed and revealed a decrease in viability associated with an increase of apoptosis; an increase of T helper cells expressing Fas and a decrease of intracellular Bcl2 protein expression. Meanwhile no effects were detected in PBMCs from healthy donors. In CD4+ T cells, transfection significantly reduced cell activation and modified the T cell differentiation, thereby decreasing both central and effector memory cells while increasing terminal effector memory cells. Interestingly, the p-miRs transfection induces a reduction of intracellular HIV p24 protein and a reduction of viral DNA integration. Finally, we evaluated the effect of synthetic (mimic) p-miR858b whose sequence is present in the MO p-miR pool and predicted to target VAV1, a protein involved in HIV-Nef binding. This protein plays a pivotal role in T cell antigen receptor (TCR) signaling, so triggering the activation of various pathways. The transfection of HIV+ PBMCs with the synthetic p-miR858b showed a reduced expression of VAV1 and HIV p24 proteins. Overall, our evidence defines putative mechanisms underlying a supplementary benefit of traditional medicine, alongside current antiretroviral therapy, in managing HIV infection in resource-limited settings where MO remains widely available.